INTRA-URBAN POPULATION MOBILITY IN THE OLD CORE OF IBADAN CITY (1974)
The interest of this thesis is in finding out whether or not there is any residential relocation in the old core of Ibadan city within the past five years (1968-1972): and if there is any, to find out the processes generating the movements. Consequently, there are two main parts to the study. The first part sought for the pattern and volume of residential relocation. It looked at the direction and distance of the movements, using an accounting model to represent the aggregate flows that were analysed. The model led to coming to grip the general structure of the movement flows, particularly the varying spatial distribution of the Population-turnover that the main focus of the thesis. The second section delt with the explanation of the variations of the Population-turnover and the reasons for movement were also sought. Firstly, an attempt was made to inductively establish the parameters of ‘strain’. The correlation and regression models were then applied to search for the relationship between these parameters and the movement rates. The procedures all confirmed that there is a singularly most important factor that can be used in the explanation of the variations in the Population-turnover. Since the importance of the perception of the people was brought out by the regression models used to explain the variations in the movement rates, the later part of the section was devoted at looking, into greater details, the ways in which the people perceive their environment. In conclusion the major findings of the study were summarized and the implication of the study for planning was suggested.